(untitled) (LEARNing Landscapes, 2011)
In this paper, we examine the history of the emerging discipline of Mind, Brain, and Education (MBE) and explore the benefits as well as the difficulties involved in integrating neuroscience into educational policy and practice. We examine the power of neuroscience to impact practice and document the rise of neuromyths. History is on the side of the new discipline of MBE, but there is still much important work to be done to make neuroscientific findings accessible, comprehensible, and relevant to educators.